Measurement of the Z(→ l+l-)γ production cross-section in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; et al. (Journal of high energy physics, 2020)
The production of a prompt photon in association with a Z boson is studied in proton-proton collisions at a centre-of-mass energy s = 13 TeV. The analysis uses a data sample with an integrated luminosity of 139 fb(-1) collected by the ATLAS detector at the LHC from 2015 to 2018. The production cross-section for the process pp -> l(+)l(-)gamma + X (l = e, mu) is measured within a fiducial phase-space region defined by kinematic requirements on the photon and the leptons, and by isolation requirements on the photon. An experimental precision of 2.9% is achieved for the fiducial cross-section. Differential cross-sections are measured as a function of each of six kinematic variables characterising the l(+)l(-)gamma system. The data are compared with theoretical predictions based on next-to-leading-order and next-to-next-to-leading-order perturbative QCD calculations. The impact of next-to-leading-order electroweak corrections is also considered.